Differences in conformational dynamics within the Hsp90 chaperone family reveal mechanistic insights - Graf, Christian; Lee, Chung-Tien; Eva Meier-Andrejszki, L.; Nguyen, Minh T. N.; Mayer, Matthias P. (Frontiers in Molecular Biosciences, 2014)
The molecular chaperones of the Hsp90 family are essential in all eukaryotic cells. They assist late folding steps and maturation of many different proteins, called clients, that are not related in sequence or structure. Hsp90 interaction with its clients appears to be coupled to a series of conformational changes. Using hydrogen exchange mass spectrometry (HX-MS) we investigated the structural dynamics of human Hsp90β (hHsp90) and yeast Hsp90 (yHsp90). We found that eukaryotic Hsp90s are much more flexible than the previously studied Escherichia coli homolog (EcHsp90) and that nucleotides induce much smaller changes. More stable conformations in yHsp90 are obtained in presence of co-chaperones. The tetratricopeptide repeat (TPR) domain protein Cpr6 causes a different amide proton protection pattern in yHsp90 than the previously studied TPR-domain protein Sti1. In the simultaneous presence of Sti1 and Cpr6, protection levels are observed that are intermediate between the Sti1 and the Cpr6 induced changes. Surprisingly, no bimodal distributions of the isotope peaks are detected, suggesting that both co-chaperones affect both protomers of the Hsp90 dimer in a similar way. The cochaperones Sba1 was found previously in the crystal structure bound to the ATP hydrolysis-competent conformation of Hsp90, which did not allow to distinguish the mode of Sba1-mediated inhibition of Hsp90’s ATPase activity by stabilizing the pre- or post-hydrolysis step. Our HX-MS experiments now show that Sba1 binding leads to a protection of the ATP binding lid, suggesting that it inhibits Hsp90’s ATPase activity by slowing down product release. This hypothesis was verified by a single-turnover ATPase assay. Together, our data suggest that there are much smaller energy barriers between conformational states in eukaryotic Hsp90s than in EcHsp90 and that co-chaperones are necessary in addition to nucleotides to stabilize defined conformational states.